Heritability and adaptive significance of the number of egg-dummies in the cichlid fish Astatotilapia burtoni - Lehtonen, Topi K. (The Royal Society, 2011)
Cichlid fishes are a textbook example of rapid speciation and exuberant diversity—this applies especially to haplochromines, a lineage with approximately 1800 species. Haplochromine males uniquely possess oval, bright spots on their anal fin, called ‘egg-spots’ or ‘egg-dummies’. These are presumed to be an evolutionary key innovation that contributed to the tribe's evolutionary success. Egg-spots have been proposed to mimic the ova of the mouthbrooding females of the corresponding species, contribute to fertilization success and even facilitate species recognition. Interestingly, egg-spot number varies extensively not only between species, but also within some populations. This high degree of intraspecific variation may appear to be counterintuitive since selection might be expected to act to stabilize traits that are correlated with fitness measures. We addressed this ‘paradox’ experimentally, and found that in the haplochromine cichlid Astatotilapia burtoni, the number of egg-spots was related to male age, body condition and dominance status. Intriguingly, the egg-spot number also had a high heritable component (narrow sense heritability of 0.5). These results suggest that the function of egg-spots might have less to do with fertilization success or species recognition, but rather relate to mate choice and/or male–male competition, helping to explain the high variability in this important trait.